ROLE OF RURAL REBELLION MOVEMENTS IN STATE ESTABLISHMENT PROCESSES IN UKRAINE (1917-1918): HISTORIOGRAPHIC OUTLINE - N. Zemzulina (Український селянин, 2018)
In this article, based on researches conducted by native scientists, one may observe the phenomenon of rural movement – resistance in Ukraine and its influence on state establishment processes in first third of XXth century. Attention is paid to the phenomenon of rural revolution, role of rural self-government and military self-organization in the process of defending ideological ideals and political choices.